Story Maps & Co. Un état de l’art de la cartographie des récits sur Internet - Sébastien Caquard; Stefanie Dimitrovas (M@ppemonde)
This article oﬀers a comparative analysis of six applications for mapping narratives on the Internet. Based on the life story of a Rwandan refugee, three main families of cartographic applications were identiﬁed: simple applications that allow the user to map stories in a standard format (ex: Tripline and Google Tour Builder); more sophisticated applications directly linked to the world of GIS), which allow the user to tell various stories using maps but which also use maps as tools for spatial and temporal analyses (ex.: ESRI Story Maps, MapStory); ﬁnally, applications that are more research oriented using narratives as databases whose analyses can help us better understand the places, their personal and intimate geographies, and the structures of the narratives that refer to them (ex.: Atlascine et Neatline).